2018
DOI: 10.1111/eip.12767
|View full text |Cite
|
Sign up to set email alerts
|

Severe conduct problems in adolescence and risk of schizophrenia in early adulthood

Abstract: Aim Reform school (RS) is a foster care institution for adolescents with severe conduct problems. Both instability of early rearing environment and severe conduct problems in adolescence may associate with later psychotic disorders. We studied whether the risk of schizophrenia in adulthood is elevated in RS adolescents, and whether it is related to the age at first foster care placement or placement instability. Methods Adult age schizophrenia spectrum disorder data from RS subjects (N = 1099) were compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…It has been reported that increasing rates of obesity among young people in the UK are a major cause of high rates of asthma, as well as in Italy and China (Manninen and Latvala et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that increasing rates of obesity among young people in the UK are a major cause of high rates of asthma, as well as in Italy and China (Manninen and Latvala et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This condition was defined by an absence of adult-age criminal record and severe mental health problems (N = 109). We used relatively wide inclusion criteria for healthy adulthood condition, as previous findings have revealed that RS background is often associated with a wide array of adult age problems (Manninen et al, 2015(Manninen et al, , 2017(Manninen et al, , 2018. After screening the eligible participants, the RS personnel approached them by sending a letter in which the study was described and a permission for the researchers to contact the participants was requested.…”
Section: Research Materials and Participantsmentioning
confidence: 99%
“…Despite rehabilitation, the current adult-age prognosis for Finnish RS adolescents is often poor. For example, adult criminality (Manninen et al, 2017), mental health problems (Manninen et al, 2011(Manninen et al, , 2018(Manninen et al, , 2021, reproductive health problems (Lehti et al, 2015) premature mortality (Manninen et al, 2015) and poor educational outcomes (Talaslampi et al, 2019) are very common in this group. Studies from other Nordic countries show similar development paths from teenage to adulthood of children and adolescents with behavioral problems including very high rates of premature death, serious involvement in crime, hospitalizations for mental-health problems, teenage parenthood, self-support problems and low educational attainment (Vinnerljung & Sallnäs, 2008).…”
mentioning
confidence: 99%